BAZNAS INTERMEDIARY FUNCTION BASED ON ZAKAT CORE PRINCIPLES - Dimas Kholiliur Rohman; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of this research is to investigate the extent of the Intermediary Function aspect of the Zakat Core Principles that are applied in the management of BAZNAS in the Sidoarjo Regency, which then will be formulated solutions to strive for optimization. The results of the study showed that the information regarding the Zakat Core Principles had not yet reached the Sidoarjo Regency BAZNAS, which certainly had not been applied in its management activities. In its collection, the BAZNAS of Sidoarjo Regency focused on ASNs, but not as muzakki. In the distribution, there were no obstacles so that the ratio of distribution to funds collected was included in the effective or even very effective category, even the synergy between BAZ and LAZ was able to be created. Government support is most needed to optimize the performance of BAZNAS on the Intermediary Function aspect.Keywords: Management of BAZNAS, BAZNAS, Zakat Core Principles, Optimization of Intermediary Function